Effect of type and volume fraction of crystallization products on the variations of electrical resistivity in Cu47Ti34Zr11Ni8 and Ti40Zr25Cu12Ni3Be20 metallic glasses. (October 2021) - Liu, Binbin; Liu, Caiyun; Jiang, Xin; Zhen, Shuying; You, Li; Ye, Feng
Abstract: The variation of electrical resistivity can be an indicative of the crystallization path for metallic glass (MG). The primary phases of Cu47 Ti34 Zr11 Ni8 and Ti40 Zr25 Cu12 Ni3 Be20 MGs are Cu 3 Ti and quasicrystal, respectively, which further influences change of electrical resistivity at the onset crystallization temperature (Tx1 ). The former shows a rapidly drop in the electrical resistivity curve along with apparent change in curve slope at Tx1, while the latter exhibits a long and continuous decrement of electrical resistivity from Tg to Tx2 without obvious change of curve slope at Tx1 . The nanoscale quasicrystal with slower growth rate indicates that the icosahedral short-range orders might exist during sample preparation, which could easily overcome crystallization obstacle and transform into the quasicrystalline phase continuously, inducing the special change of the Ti40 Zr25 Cu12 Ni3 Be20 MG. Meanwhile, the TCR of the crystalline/glass composite materials depends on the volume fraction of crystalline phase. When the volume fraction of crystalline phases is small, the TCR is still determined by the residual amorphous phase. Highlights: Vriation of electrical resistivity can be an indicative of crystallization path for MGs. A long and continuous decline of resistivity from Tg to Tx2 was found in the Ti40 Zr25 Cu12 Ni3 Be20 MG. Unique resistivity change means similar electronic structure between the glass and quasicrystal. TCR is determined by both types of crystallization products and their volume fraction.